Sinterização a laser e caracterização óptica de cerâmicas de SrAl2O4:Eu, Dy - Souza, Natalilian Roberta da Silva (2015)
Materials with long-lasting phosphorescence has attracted much attention due to its great potential for practical applications in various fields, such as electronic displays , radiation detectors , digital radiography , optical memories and storing images . In particular, the doped strontium aluminate europium and dysprosium (SrAl2O4: Eu, Dy) presents with phosphorescence lifetime of up to 10h. Thus, in the present study, we aimed to study the properties of phosphorescent aluminate ceramics doped with different concentrations of Eu and Dy (SrAl2O4: Eu, Dy) laser sintered strontium. For this the powder synthesis by the polymeric precursor method was performed, and set the conditions for laser sintering of ceramic bodies to be studied. Powders SrAl2O4: Eu, Dy were synthesized by the polymeric precursor method (Pechini method) and sintered using the technique of laser sintering. In this method a CO2 laser is used as a primary heat source for sintering, enabling processing with high rates of heating and cooling. To characterize employ the techniques of Differential Thermal Analysis, Thermogravimetry , X rays diffraction , Raman spectroscopy , scanning electron microscopy and photoluminescence. For the synthesis, the solution was pre- calcined at 600 ° C/5h then the resulting powder was calcined in an agate mortar and sintered in an electric furnace and a laser. For sintering the powders were uniaxially pressed and sintered via laser processing and, for comparison, conventionally in an electric furnace at 1250 ° C/1h. The laser sintered ceramics show only the monoclinic phase and a long-lasting phosphorescence, thus showing the effectiveness of this sintering technique. Since the conventional sintered ceramics have a monoclinic phases and mixtures of the hexagonal SrAl2O4 and low luminescent intensity.